BALINESE ACTIONS AND SOLIDARITY REGARDING OGOH-OGOH IN BANJAR UNTAL-UNTAL: A SOCIOLOGY OF RELIGION PERSPECTIVE - Nole, Otniel Aurelius (UHN I Gusti Bagus Sugriwa Denpasar, 2024)
Ogoh-ogoh is a typical Balinese activity that can be found once a year. Ogoh-ogoh is characterized as a sculptural artwork resembling a creepy creature’s image as it symbolizes bhuta kala as an evil entity. Balinese people celebrate the ogoh-ogoh parade, burn them to avoid negative influences and continue life with silence and positivity in the Saka New Year (Nyepi). Ogoh-ogoh is also a tradition that attracts attention because it is displayed with the splendor and beauty of stunning artwork. Of course, it reflects the behavior of Balinese people, whom residents of Banjar Untal-Untal also celebrate. The purpose of this research was to analyze the actions and solidarity of Balinese people regarding ogoh-ogoh in Banjar Untal-Untal from the perspective of the sociology of religion. This research method was qualitative with a case study design. The researcher collected data through interviews and observation. This research showed that the preparation, making, and implementation of ogoh-ogoh exists because of the involvement of people who act in solidarity. Max Weber’s theory of social action and Emile Durkheim’s theory of social solidarity had relevance to the ogoh-ogoh parade. In social action and solidarity, religious adherents, specifically Christians and Hindus, synergized and supported each other.